Analisis Pemahaman Anggota Legio Maria Paroki Santo Simon Petrus Tarus Tentang Maria dan Pentingnya Pelatihan Kitab Suci Bagi Legioner - Senda, Siprianus S.; Silab, Theodorus A.; Kosat, Oktovianus (Jayapangus Press, 2024)
Legio Maria is a Catholic lay organization that is devoted to the Virgin Mary. As devotees of Our Lady, members of the Legion of Mary should have an adequate understanding of Our Lady who is believed in and accepted as the Supreme Commander of the Legion of Mary. However, in reality, there are still many members of the Legion of Mary who do not have adequate knowledge and understanding of Mary in the holy scriptures. This research aims to determine the extent of understanding of the members of the Legio Maria Parish of Saint Simon Peter Tarus about the Virgin Mary and provide an understanding of Mary in the holy scriptures. The method used is field research combined with library research. The results of the research state that most members of the Legion of Mary in this parish do not understand the Virgin Mary according to the information in the holy books, especially the four Gospels. As a solution to this lack of understanding, the author offers the importance of scriptural training for legionaries by explaining the description of Mary in the four Gospels based on selected texts. The results of this research became a starting point for further activities, namely community service in the form of basic holy book training courses for members of the Legio Maria Parish of Saint Simon Peter Tarus.